2019
DOI: 10.1371/journal.pone.0222065
|View full text |Cite
|
Sign up to set email alerts
|

Plasma total fibroblast growth factor 23 levels are associated with acute kidney injury and mortality in children with acute respiratory distress syndrome

Abstract: Acute respiratory distress syndrome (ARDS) has high rates of mortality and multisystem morbidity. Pre-clinical data suggest that fibroblast growth factor 23 (FGF23) may contribute to pulmonary pathology, and FGF23 is associated with mortality and morbidity, including acute kidney injury (AKI), in non-ARDS cohorts. Here, we assess whether FGF23 is associated with AKI and/or mortality in a cohort of 161 pediatric ARDS patients. Plasma total (intact + C-terminal) FGF23 and intact FGF23 concentrations were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…ARDS pathobiology is characterized by inflammation, loss of the alveolar epithelial, and lung vascular endothelial permeability barriers, dysregulated coagulation, and fibrosis. Recent advances related to individual and combinations of plasma biomarkers indicative of many of these aspects of PARDS pathobiology and studies aimed at identifying subphenotypes at greater risk of worse clinical outcome and/or response to therapy are described in the sections below (5, 22, 45, 49, 70, 96–139). Subphenotype identification offers enhanced prognostic ability beyond what bedside physiologic biomarkers and/or PARDS trigger (e.g., pneumonia, sepsis, trauma, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ARDS pathobiology is characterized by inflammation, loss of the alveolar epithelial, and lung vascular endothelial permeability barriers, dysregulated coagulation, and fibrosis. Recent advances related to individual and combinations of plasma biomarkers indicative of many of these aspects of PARDS pathobiology and studies aimed at identifying subphenotypes at greater risk of worse clinical outcome and/or response to therapy are described in the sections below (5, 22, 45, 49, 70, 96–139). Subphenotype identification offers enhanced prognostic ability beyond what bedside physiologic biomarkers and/or PARDS trigger (e.g., pneumonia, sepsis, trauma, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…A multiple logistic regression model incorporating OI, IL-8, and TNFR2 was superior to a model of OI alone in predicting the composite outcome of mortality or severe morbidity (AUROC [95% CI], 0.77 [0.70–0.83] vs 0.70 [0.62–0.77]; p = 0.042) (108). In the same cohort of children, higher levels of total fibroblast growth factor 23 on day 1 of ARDS were associated with both acute kidney injury and mortality and mediation analysis suggested that this effect was likely partially mediated by inflammation (120). Interestingly, children in this cohort with a history of hematopoietic cellular transplantation (HCT) had higher levels of IL-8, IL-18, IL-10, and TNFR2 (108).…”
Section: Resultsmentioning
confidence: 99%
“…Search in databases resulted in 987 non-duplicate articles. After screening, 21 studies [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ] were included in the current meta-analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For human samples, there are commercial assays to measure both C-terminal FGF23 and intact FGF23 [50]. The C-terminal assay captures both intact FGF23 and C-terminal FGF23 fragments, thus measuring total (intact + fragmented) FGF23 concentrations.…”
Section: Fgf23 Productionmentioning
confidence: 99%